PENDIDIKAN MULTIKULTURAL BAM SEBAGAI MUATAN LOKAL UNTUK PEMBENTUKAN KARAKTER DI SUMATERA BARAT - Pratama, Robbyanandri; Khairunnisa, Nila Aulia (JURNAL DWIJA KUSUMA, 2025)
Multicultural Education of BAM as Local Content for Character Development in West Sumatra" aims to analyze the role of multicultural education based on local wisdom in Budaya Alam Minangkabau (BAM) as a local content subject in shaping students' character in West Sumatra. This study employs a library research method, utilizing data sources from books and relevant scientific journals. The findings indicate that multicultural education based on Minangkabau customary values, such as Adat Basandi Syara', Syara' Basandi Kitabullah and Alam Takambang Jadi Guru, strengthens cultural identity and fosters students’ ethical behavior, tolerance, and adaptability to social diversity. However, challenges such as modernization, globalization, and the declining role of traditional leaders threaten the continuity of these cultural values. Therefore, synergy among families, schools, the government, and the community is crucial to ensuring the sustainability of multicultural education based on local wisdom.